Adsorption of Pb (II) from Aqueous Solution using Nypa Fruticans Activated Carbon (NFAC) - Muhammad Kamal Rusyaidi, Mohtar; Inawati, Othman; Nur’Anisa, Roslan; Yiin, Chung Loong; Dayang Salyani, Abang Mahmod; Norazlina, Bateni; Astri, Rinanti (Semarak Ilmu Publishing, 2025)
This study explored the removal of Pb from aqueous solutions with Nypa Fruticans activated carbon (NFAC), derived from abundant and underutilized biomass, as a novel and sustainable adsorbent. The shell of Nypa Fruticans was carbonized and chemically activated using the zinc chloride method. Scanning Electron Microscope (SEM-EDX) was utilised to study the physical properties of NFAC. The chemical properties of the activated carbon were studied with Fourier-Transform Infrared Spectroscopy (FTIR). The study aimed to examine the effectiveness of absorbent materials in various applications. Moreover, the study investigated the influence of Pb (II) intensity, pH levels, Nypa Fruticans activated carbon dosage, and contact duration on Pb (II) removal. Based on the findings of the experiment, it was found that the most effective conditions for removing Pb (II) were as follows: Pb (II) concentration was ten ppm, which resulted in a 70.22% removal efficiency. A dose of 0.5 grams of NFAC was used, resulting in a 77.25% removal efficiency for Pb (II). When the pH was adjusted to 5, adsorption of 96.83% was achieved for Pb (II). The contact time between NFAC and Pb (II) was 120 minutes, resulting in a 93.49% adsorption of Pb (II). To calculate adsorption capacity, Langmuir and Freundlich isotherms were applied, and modelling adsorption kinetics was represented with pseudo first order and pseudo second order theorem. While traditional Langmuir and Freundlich isotherm models did not adequately fit the data, pseudo second order kinetics provided a strong fit (R² = 0.99), indicating chemisorption as the dominant mechanism.